The ghosts of Gombe : a true story of love and death in an African wilderness - Peterson, Dale (University of California Press, 2018)
"This book, written by the author of the "definitive" biography of primatologist Jane Goodall, presents in sweeping detail the story of a group of young volunteers and students doing animal behavior research on chimpanzees, baboons, and red colobus monkeys at Dr. Goodall's research site in Tanzania's Gombe Stream National Park during the late 1960s. Goodall, who began her work in the summer of 1960, was originally sponsored by the great paleontologist Louis Leakey and funded by the National Geographic Society. Her early studies of chimpanzees soon made her world famous as one of the great pioneers in primatology, and she began working to transform her original tented camp into a major field station for animal studies. Then came a tragic event that marked the final summer of that promising first decade and is the focus of this book. At around noon, on Saturday, July 12, 1969, Ruth Davis, a young American working at Gombe as a volunteer, walked out of camp to follow a chimpanzee into the forest and never returned. Her body was found six days later floating in a pool at the base of a high waterfall. The Ghosts of Gombe explores the social tensions that developed among the small community of researchers during 1968 and 1969; considers thoroughly how the death might have happened; and describes the painful personal consequences for some of the surviving researchers."--Provided by publisher.